Peran Bimbingan Keagamaan pada Remaja untuk Mengurangi Dampak Penyalahgunaan NAPZA - Miladiyah Nur Rohamah; Tjetjep Fachruddin; Abdul Mujib (Department of Islamic Guidance and Counseling, Faculty of Dakwah and Communication, UIN Sunan Gunung Djati Bandung, 2018)
The purpose of this study is to know the process, the role and the achievements of the religious guidance process of Baitul Ummah Foundation in reducing drug abuse in adolescents. The method used in the core research is descriptive method. The data found that process of implementing religious guidance in the Baitul Ummah Foundation consists of mentors, materials, media, methods. The result of this guidance that teenagers begin to live better by not using the drug again and if seen from the spiritual condition, the teenager began to perform his duty back as a servant of God with the good that is by performing the obligations of an Islamic people such as praying, fasting and other etc. Keywords: guidance; religion; youth; drugs. Penelitian ini mengungkapkan proses, peran, dan capaian bimbingan keagamaan yang dilakukan Yayasan Baitul Ummah dalam mengurangi penyalahgunaan NAPZA pada remaja. Metode yang digunakan dalam penelitian ini yaitu metode deskriptif. Dalam proses pelaksanaan bimbingan keagamaan di Yayasan Baitul Ummah terdapat pembimbing, materi, media, dan metode. Hasil dari bimbingan di Yayasan Baitul Ummah diketahui remaja mulai menjalani kehidupanya yang lebih baik dengan tidak menggunakan NAPZA kembali serta jika dilihat dari kondisi rohani, remaja mulai melakukan kewajibannya kembali sebagai hamba Allah dengan baik yaitu melaksanakan kewajiban seperti sholat, puasa dan sebagainya. Kata Kunci: bimbingan; keagamaan; remaja; NAPZA.